Whole exome sequencing identified a homozygous novel variant in DOP1A gene in the Pakistan family with neurodevelopmental disabilities: case report and literature review - Zhang, Wei; Tariq, Muhammad; Roy, Bhaskar; Shen, Juan; Khan, Ayaz; Altaf Malik, Naveed; He, Sijie; Baig, Shahid Mahmood; Fang, Xiaodong; Zhang, Jianguo (Frontiers in Genetics, 2024)
Hereditary neurodevelopmental disorders (NDDs) are prevalent in poorly prognostic pediatric diseases, but the pathogenesis of NDDs is still unclear. Irregular myelination could be one of the possible causes of NDDs.Here, whole exome sequencing was carried out for a consanguineous Pakistani familyy with NDDs to identify disease-associated variants.The co-segregations of candidate variants in the family were was validated using Ssanger sequencing. The potential impact of the gene on NDDs has been supported by conservation analysis, protein prediction, and expression analysis. A novel homozygous variant, DOP1A(NM_001385863.1):c.2561A>G was identified. It was concluded that the missense variant might affect the protein-protein binding sites of the critical MEC interaction region of DOP1A, and DOP1A-MON2 may cause stability deficits in Golgiendosome protein traffic. cause stability deficits to the possible Golgi-endosome protein traffic DOP1A-MON2. Myelination proteins proteolipid protein (PLP) and glycoprotein (MAG) could be targets of the DOP1A-MON2 Golgi-endosome traffic complex, especially during in the fetal stage and the early developmental stages. This further supports the perspective that disorganized myelinogenesis due to congenital DOP1A deficiency might cause neurodevelopmental disorders (NDDs).Our case study revealed the potential pathway of the myelinogenesisrelevant NDDs and identified DOP1A as a potential NDDs--relevant gene in humans.